Biscoitos integrais: legislação pertinente e percepção do consumidor - Thayla Diana Parise; Marceli Pitt Coser (Universidade do Estado do Rio de Janeiro, 2020)
Countless benefits are attributed to whole grain foods, especially due to the concentration of dietary fiber in these products. It is widely known that whole grain cookies are part of the consumers' diet, that food labeling is the primary means of communication between producers and consumers, and that a relevant legislation for this class of food is required. Thus, the present study aimed to verify whether nutrition claims and/or terms displayed on the labels of whole grain cookies are in compliance with the applicable labeling legislation, and also to ascertain consumer's perception on these claims as well as their preference for and consumption of these products. The study was carried out in three supermarkets in the city of Videira-SC, split into two stages: label analysis through a checklist and administration of a questionnaire to consumers. Results showed non-compliances, especially the use of terms not foreseen by the law, which could mislead consumers. Regarding the perception of consumers, they mostly believe that a product may contain at least 50% of whole grains to be called a whole grain food, and associate them with health benefits. It is necessary to develop and promote nutrition education actions as well as constitutional rigidity and compliance with the applicable legislation, and new and relevant technical standards for whole grain foods in order to improve requirements for this class of food.